(untitled) (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2004)
In this paper it is shown that: 1) There exists such a tt-degree which contains infinitely many m-degrees of the type of ω^k for any positive natural number k; 2) There exists such a tt-degree which contains infinitely many m-degrees of the type of Q of rational numbers.